2014
DOI: 10.1021/jp501319e
|View full text |Cite
|
Sign up to set email alerts
|

Chelate Effects in Glyme/Lithium Bis(trifluoromethanesulfonyl)amide Solvate Ionic Liquids. I. Stability of Solvate Cations and Correlation with Electrolyte Properties

Abstract: To develop a basic understanding of a new class of ionic liquids (ILs), "solvate" ILs, the transport properties of binary mixtures of lithium bis(trifluoromethanesulfonyl)amide (Li[TFSA]) and oligoethers (tetraglyme (G4), triglyme (G3), diglyme (G2), and monoglyme (G1)) or tetrahydrofuran (THF) were studied. The self-diffusion coefficient ratio of the solvents and Li(+) ions (Dsol/DLi) was a good metric for evaluating the stability of the complex cations consisting of Li(+) and the solvent(s). When the molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
326
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 223 publications
(361 citation statements)
references
References 59 publications
35
326
0
Order By: Relevance
“…[8][9][10] Of particular interest are the stoichiometric mixtures of glymemetal salts because they often form a low-melting complex with long-lived complex cation through the chelate effect. 11,12 Many glyme-metal salt complexes have been studied, ranging from alkali metal salts (Li, 13 Na, 14 and K 15 ) to alkali earth metal salts (Mg 16 and Ca 17 ). However, most of the complexes yielding solvate ILs comprise bis(trifluoromethensulfonyl) amide (TFSA) salts owing to their good thermal and electrochemical stabilities, their ability to lower the melting point, and weakly coordinating property that ensures strong glyme-metal ion interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Of particular interest are the stoichiometric mixtures of glymemetal salts because they often form a low-melting complex with long-lived complex cation through the chelate effect. 11,12 Many glyme-metal salt complexes have been studied, ranging from alkali metal salts (Li, 13 Na, 14 and K 15 ) to alkali earth metal salts (Mg 16 and Ca 17 ). However, most of the complexes yielding solvate ILs comprise bis(trifluoromethensulfonyl) amide (TFSA) salts owing to their good thermal and electrochemical stabilities, their ability to lower the melting point, and weakly coordinating property that ensures strong glyme-metal ion interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A structurally related series of concentrated mixtures of Li[TFSA] and oligoethers, including G4, G3, diglyme (G2), and monoglyme (G1) or tetrahydrofuran (THF), were studied to clarify the chelate effect on the formation of the stable complex cation in the molten state. 25 In Fig We also found that the presence or absence of the free glyme in [Li(glyme) n ]X strongly correlated with the thermal and electrochemical properties. Because the thermal and oxidative stability of the glymes were enhanced by the strong complex formation, the increase of T d and the electrochemical oxidative stability were less pronounced for [Li(glyme) n ]X classified as the concentrated solutions.…”
Section: ¹1mentioning
confidence: 55%
“…Because the thermal and oxidative stability of the glymes were enhanced by the strong complex formation, the increase of T d and the electrochemical oxidative stability were less pronounced for [Li(glyme) n ]X classified as the concentrated solutions. 25,26 Again, [Li(G3)]X and [Li(G4)]X with perfluorinated sulfonylamide anions met the criteria related to the structure and properties of the solvate ILs.…”
Section: ¹1mentioning
confidence: 98%
“…[89][90][91][92] We explored a variety of such combinations and found that, in certain combinations, these materials have similar properties to conventional aprotic ILs. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] We conclude that these mixtures can be categorized as "solvate ILs," i.e., liquids consisting of a salt and a solvent that strongly coordinates with cations or anions to form stable solvate ions. 110 Detailed studies of the solvate IL on the transport properties, [93][94][95][96][97][98][99] spectroscopic, [99][100][101][102][103] crystallographic, [100][101][102][103] electrochemical, [94][95][96]104,105 quantum mechanical characterizations, [106][107][108]…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 91%
“…The formation of solvate ILs is affected by the structure of the lithium salt anions 97,99 and glyme molecules. 98 Furthermore, the transport properties of solvate ILs are much better than conventional Li-doped ILs 113 and can be further improved by dilution with solvents that do not disrupt the solvate structures. 117,122 Consequently, solvate ILs are suitable for use as electrolytes in lithium ion batteries [111][112][113][114] and lithium-sulfur batteries.…”
Section: © -Conducting Ils and Solvate Ilsmentioning
confidence: 99%